'Do i want to face the offender?': Malaysian victims' motivation for participating in restorative justice. Issue 3 (3rd July 2021) - Mohammad, Taufik; Azman, Azlinda
ABSTRACT: The objective of this study is to understand Malaysian victims' motivations for participating in restorative justice programmes via their views on three core elements of restorative justice: meeting and dialogue, reparation of harm and apology. In this mixed-design study, 63 Malaysian victims of crimes were interviewed. The findings suggest that, in general, there was a willingness to participate and that among the victims' main motivations for participation were the desire to express their voice and to understand their victimisation. The findings of this study lay the groundwork for a new policy in Malaysia and contribute to understanding how restorative justice helps Malaysian victims of crime achieve well-being post-victimisation, as well how this can be achieved.